Dynamics of near borehole zone while drilling poroelastic layer - Shelukhin, V. V.; Eltsov, I. N. (Geofizicheskiy Zhurnal, 2012)
Mathematical model of strain state dynamics has been proposed, which makes possible to detect how stresses and strains impact filtration flows near the borehole. Behavior of both invasion front and mud-cake growth has been studied. Comparison with the earlier obtained results for a rigid rock frame has been made.